Investigations associated with the 2020/21 highly pathogenic avian influenza epizootic in wild birds in Great Britain. (5th November 2021) - Duff, Paul; Holmes, Paul; Aegerter, James; Man, Cat; Fullick, Ed; Reid, Scott; Lean, Fabian; Núñez, Alex; Hansen, Rowena; Tye, Joanna; Stephan, Lévon; Brown, Ian; et al.
Abstract : This focus article has been prepared by Paul Duff, Paul Holmes, James Aegerter, Cat Man, Ed Fullick, Scott Reid, Fabian Lean, Alex Núñez, Rowena Hansen, Joanna Tye, Lévon Stephan and Ian Brown of the APHA and Caroline Robinson of SRUC.